Coma-corrected rapid single-particle cryo-EM data collection on the CRYO ARM 300 - Efremov, Rouslan G. (Acta Crystallogr D Struct Biol, 2021)
Single-particle cryogenic electron microscopy has recently become a major method for determining the structures of proteins and protein complexes. This has markedly increased the demand for throughput of high-resolution electron microscopes, which are required to produce high-resolution images at high rates. An increase in data-collection throughput can be achieved by using large beam-image shifts combined with off-axis coma correction, enabling the acquisition of multiple images from a large area of the EM grid without moving the microscope stage. Here, the optical properties of the JEOL CRYO ARM 300 electron microscope equipped with a K3 camera were characterized under off-axis illumination conditions. It is shown that efficient coma correction can be achieved for beam-image shifts with an amplitude of at least 10 µm, enabling a routine throughput for data collection of between 6000 and 9000 images per day. Use of the benchmark for the rapid data-collection procedure (with beam-image shifts of up to 7 µm) on apoferritin resulted in a reconstruction at a resolution of 1.7 Å. This demonstrates that the rapid automated acquisition of high-resolution micrographs is possible using a CRYO ARM 300.